Gut-liver axis at the frontier of host-microbial interactions - Brandl, Katharina; Kumar, Vipin; Eckmann, Lars (American journal of physiology: Gastrointestinal and liver physiology, 2017)
Liver and intestine are tightly linked through the venous system of the portal circulation. Consequently, the liver is the primary recipient of gut-derived products, most prominently dietary nutrients and microbial components. It functions as a secondary “firewall” and protects the body from intestinal pathogens and other microbial products that have crossed the primary barrier of the intestinal tract. Disruption of the intestinal barrier enhances microbial exposure of the liver, which can have detrimental or beneficial effects in the organ depending on the specific circumstances. Conversely, the liver also exerts influence over intestinal microbial communities via secretion of bile acids and IgA antibodies. This mini-review highlights key findings and concepts in the area of host-microbial interactions as pertinent to the bilateral communication between liver and gut and highlights the concept of the gut-liver axis.